1) 36 - 12b + b² = 6² - 2 * 6 * b + b² = (6 - b)² = (6 - b)(6 - b)
2) (a³ + 2)(3 - a) - 3(a³ + 2) = (a³ + 2)(3 - a - 3) = - a(a³ + 2)
1.
Используя формулу сокращённого умножения.
2.
1) 36 - 12b + b² = 6² - 2 * 6 * b + b² = (6 - b)² = (6 - b)(6 - b)
2) (a³ + 2)(3 - a) - 3(a³ + 2) = (a³ + 2)(3 - a - 3) = - a(a³ + 2)
1.![36-12b+b^{2} = (6-b)^{2} = (6-b)(6-b)](/tpl/images/0972/4827/19a28.png)
Используя формулу сокращённого умножения.
2.![(a^{3}+2) * (3-a) - 3 * (a^{3}+2) = (a^{3} + 2) * (3-a-3) = (a^{3}+2) * (-a) = -a * (a^{3} + 2)](/tpl/images/0972/4827/1bbd2.png)